Clinical problems in oncology : a practical guide to management - Moorcraft, Sing Yu; Lee, Daniel L. Y.; Cunningham, David, 1954 December 4- (Chichester, West Sussex : Wiley-Blackwell, 2014)
"Clinical Problems in Oncology: A Practical Guide to Management is an easy-to-use, compact reference guide packed with essential practical information on how to manage oncological emergencies as well as the side effects and complications of cancer and its treatment. The main objective is for the book to become a "go-to" reference guide for UK-based oncology registrars ("fellows" in the USA) and house officers seeking information on how to manage and deal with oncological problems at the point of care, on the wards as well as in outpatient clinics. However, the book is prepared in such a way that it will be of use to other medical professionals in the UK or Europe who encounter oncology patients in the course of their work. The book covers the most common scenarios encountered in the day-to-day management of both clinical and medical oncology patients and collates useful information that is currently scattered around in various different places. For example, if a patient was admitted neutropenic with abdominal pain, vomiting and diarrhoea then the doctor may wish to access the following resources: Guidelines on when to use GCSFPharmacy details regarding the toxicities associated with their chemotherapy (i.e. does their chemotherapy regime often cause diarrhoea?) Details on how to grade toxicity A review article on the management of chemotherapy-induced diarrhoea Pharmacy monographs on the correct prescribing of electrolyte replacement Palliative care guidance on how to switch oral opiates to IV opiates or how to start a syringe driverIt is often difficult to find this kind of specific, practical information in a timely manner, even using the Internet! Clinical Problems in Oncology collates all of this information and puts it at the practitioner's fingertips, making heavy use of bullet points, tables and flowcharts in order to assist users in finding the information they need quickly. While not replacing local cancer treatment guidelines, this exciting new book provides a truly useful starting point for the management of oncology patients"--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Tumors -- Handbooks, manuals, etc; Clinical medicine -- Methods -- Handbooks, manuals, etc; Neoplasms; Clinical Medicine -- methods; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Handbooks; Electronic books; Electronic books